Characterization and melt spinning of poly (lactic acid)/poly (ethylene glycol) blends - Mohd Akhir, Nur atiqah; Othman, Maizatulnisa; Fachmi Buys, Yose; Shaffiar, Norhashimah; Jimat, Dzun Noraini; Syed Shaharuddin, Sharifah Imihezri (Faculty of Engineering International Islamic University Malaysia, 2021)
: In this study, melt blended compositions of pure PLA with additions of polyethylene glycol (PEG) up to 30 wt% were prepared. Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), and thermogravimetric analysis (TGA) were used to investigate the properties of PLA/PEG blends, such as structural, thermal, and morphological properties. The results showed that further increments of PEG cause the -OH group of PLA/PEG blends to show a broad peak, indicating that there is hydrogen bonding interaction between PEG and PLA chains. DSC result revealed that the addition of PEG decreases the glass transition temperature from 57 °C to 46 °C and crystallization temperature from 107 °C to 87 °C. Such trends suggest enhanced chain mobility of PLA chains. TGA thermograms showed that further additions of PEG into PLA resulted in a consistent shift to lower temperature and decrease in thermal stability. Optical microscopy (OM) and scanning electron microscopy (SEM) observations of the melt spun PLA/PEG microfibers revealed that the diameter of the microfibers averaged between 15 to 80 microns.